BUILDING QUALITY CULTURE AT THE UNIVERSITY OF CULTURE, SPORTS AND TOURISM CULTURE THAT IS RELIABLE WITH CURRENT PRACTICES - LAN, NGUYEN THI (International Journal of Social and Humanities Extension(IJSHE), 2022)
The global trend of education competition has made quality assurance a prerequisite activity, and this is an important first step in the process of building a quality culture at higher education institutions. To ensure the quality of education is sustainable, it is necessary to build and develop a quality culture. Within the scope of this article, the author proposes several measures to contribute to building and developing a culture of educational quality in the school..